A number of legume species were inoculated with Phakopsora pachyrhizi Syd. the causal agent of soybean rust. The species showing rust symptom were Pachyrhizus erosus, Crotalaria juncea, Glycine max var. si Nyonya, Vigna unguiculata, Phaseolus vulgaris (green bean), P. radiatus (mung bean), P. aureus, Psophocarpus tetragonolobus, Vigna umbellata and Calopogonium mucunoides. - Meity Sinaga (Buletin Hama dan Penyakit Tumbuhan, 1979)
A number of legume species were inoculated with Phakopsora pachyrhizi Syd. the causal agent of soybean rust. The species showing rust symptom were Pachyrhizus erosus, Crotalaria juncea, Glycine max var. si Nyonya, Vigna unguiculata, Phaseolus vulgaris (green bean), P. radiatus (mung bean), P. aureus, Psophocarpus tetragonolobus, Vigna umbellata and Calopogonium mucunoides.